Pemberdayaan masyarakat dalam pemanfaatan limbah padat tahu sebagai bahan baku pupuk organik ramah lingkungan - Maharani Kusumaningrum; Nadya Alfa Cahaya Imani; Ria Wulansarie; Vera Noviana Sulistyawan; Indrasukma Permanadewi; Elvina Belva Fithriyah; Berliana Putri Rahmalia; Hidayatul Munadhiroh; Hasna Rifqi Nabila; Anin Bimarhamah (STAI Auliaurrasyidin Tembilahan, 2025)
The tofu industry generates a large amount of solid waste that is often underutilized and may pollute the environment if left unmanaged.